2021
DOI: 10.1002/alr.22901
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of clinical characteristics in eosinophilic chronic rhinosinusitis with nasal polyps: A cross‐sectional study in the Chinese population

Abstract: Background Eosinophilic chronic rhinosinusitis with nasal polyps (ECRSwNP) is a refractory subtype of chronic rhinosinusitis with nasal polyps (CRSwNP), with clinical characteristics differing from those of non‐ECRSwNP. We aimed to explore the predictive value of clinical characteristics, including medical history, symptoms, and signs, prior to ECRSwNP diagnosis, and to develop a nomogram for use in clinical practice. Methods A total of 502 patients with CRSwNP were enrolled. Based on the degree of eosinophili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…[8] However, none of these reports were conducted exclusively in patients with CRSwNP, which is of utmost importance, as these patients have a fluctuating sense of smell. [9] It has also been reported that these patients who are more aware of their sense of smell obtain better correlations between the subjective and instrumental assessment. [8] In fact, the frequency of unawareness of OD was only 16% in CRS, [10] much lower than the 30% reported by Lötsch and Hummel(8) in a non-selected population, or 77% in elderly individuals.…”
Section: Introductionmentioning
confidence: 90%
“…[8] However, none of these reports were conducted exclusively in patients with CRSwNP, which is of utmost importance, as these patients have a fluctuating sense of smell. [9] It has also been reported that these patients who are more aware of their sense of smell obtain better correlations between the subjective and instrumental assessment. [8] In fact, the frequency of unawareness of OD was only 16% in CRS, [10] much lower than the 30% reported by Lötsch and Hummel(8) in a non-selected population, or 77% in elderly individuals.…”
Section: Introductionmentioning
confidence: 90%
“…CRSwNP is generally divided into eosinophilic CRSwNP (ECRSwNP) and noneosinophilic CRSwNP (nECRSwNP) based on the degree of eosinophil infiltration ( 3 5 ). Caucasian CRSwNP patients tend to exhibit greater eosinophilic inflammation than Asian patients, while the prevalence of ECRSwNP is increasing in Asian countries ( 6 , 7 ). Currently, the etiology of CRSwNP has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that the comorbidity rate of asthma and allergic rhinitis were higher in the eCRSwNP subgroup than in the non-eCRSwNP subgroup. 17 18 However, Hu et al . 19 found that although the association of eCRSwNP with asthma is widely accepted, there was no significant statistical difference between the rate of coexistence of asthma in eosinophilic and non-eCRSwNP.…”
Section: Introductionmentioning
confidence: 99%